Assessment of the speed and ease of insertion of three supraglottic airway devices by paramedics: a manikin study. Issue 11 (1st June 2010) - Castle, Nick; Owen, Robert; Hann, Mark; Naidoo, Raveen; Reeves, David
Abstract : Background: Control of the airway is a priority during cardiopulmonary resuscitation and/or following a failed intubation attempt. Supraglottic airway devices provide more effective airway management than bag-valve-mask-ventilation (BVMV) and can be effectively used by non-anaesthetists. Methods: 36 paramedic students were timed to ascertain how long it took them to place an Igel, laryngeal mask airway (LMA) or laryngeal tube airway (LTA) into a manikin. Following insertion, students were interviewed to see which device they preferred and why. Results: The Igel was consistently the fastest airway device, taking a mean of 12.3 s (95% CI 11.5 to 13.1) to insert, the LTA took a mean time of 22.4 s (95% CI 20.3 to 24.5) and the LMA 33.8 s (95% CI 30.9 to 36.7). 63% of students would choose the Igel as their preferred intermediate airway device, stating ease of use and speed of insertion as the primary reasons. Conclusion: The ease and speed at which a supraglottic airway can be inserted means that it is a viable alternative to the use of the BVMV.